Microbiological Surveillance of Biogas Plants: Targeting Acetogenic Community - Singh, Abhijeet; Moestedt, Jan; Berg, Andreas; Schnürer, Anna (Frontiers in Microbiology, 2021)
Acetogens play a very important role in anaerobic digestion and are essential in ensuring process stability. Despite this, targeted studies of the acetogenic community in biogas processes remain limited. Some efforts have been made to identify and understand this community, but lack of a reliable molecular analysis strategy makes detection of acetogenic bacteria tedious. Recent studies suggest that screening of bacterial genetic material for formyltetrahydrofolate synthetase (FTHFS), a key marker enzyme in the Wood-Ljungdahl pathway, can give a strong indication of presence of putative acetogens in biogas environments. In this study, we applied an acetogen-targeted analyses strategy developed previously by our research group in microbiological surveillance of commercial biogas plants. The surveillance comprised high-throughput sequencing of FTHFS gene amplicons and unsupervised data analysis with the AcetoScan pipeline. The results showed differences in acetogenic community structure related to feed substrate and operating parameters. They also indicated that our surveillance method can be helpful in detection of community changes before observed changes in physico-chemical profiles and that frequent high-throughput surveillance can assist in management towards stable process operation, thus improving the economic viability of biogas plants. To our knowledge, this is the first study to apply a high-throughput microbiological surveillance approach to visualise the potential acetogenic population in commercial biogas digesters.